PENGARUH KEPEMIMPINAN PELAYAN DAN BUDAYA ORGANISASI TERHADAP PENGELOLAAN KONFLIK - Tri Widyastuti (Cakrawala - Jurnal Humaniora, 2016)
Conflict, both internal and external conflicts, can cause problems in organizationbecause of differences in purpose, interests, personalities, experiences, perceptions,and motivations among individuals or groups in the organization. Every leader needsto apply conflict management to curb the excessive nature of competition andundermine the spirit of synergism organization. Through servant leadership style andorganizational culture, leaders are expected to be able to apply conflict managementin accordance with the circumstances in the organization. The research proves thatthere is an influence between servant leadership and organizational culture toconflict management in PT. Indonesia Power - UBH at Jakarta. The evident from theresults obtained from the calculation showed that there is a significant influencepartially and simultaneously of servant leadership and culture organization towardsconflict management. It can be concluded that the improvement, socialization andimplementation of servant leadership and organizational culture are important toimprove the leaders’ conflict management skills in PT. Indonesia Power - UBH,Jakarta.